Long-Term Outcomes of Diabetic Macular Edema Treatment with Intravitreal Fluocinolone Acetonide: A Real-World Experience - Jorge Miguel Cagigal da Silva Gomes (2021)
Purpose To report on the safety and efficacy of intravitreal fluocinolone acetonide (FAc) in eyes with chronic diabetic macular edema (DME). Methods This is a retrospective observational study of 16 eyes with chronic DME that had the intravitreal FAc implant for at least 3 years. The main outcome collected from clinical records were central macular thickness (CMT), visual acuity (VA), intra-ocular pressure (IOP) and retinal nerve fiber layer (RNFL) thickness. Results This study included 16 eyes from 12 patients with a mean age at the time of the implant of 70 years. Regarding efficacy, CMT had a statistically significant decrease (p=0,02) while VA remained stable overtime (p=0,13). Concerning safety, mean IOP did not significantly differ throughout the follow-up time (p=0,26), however, the number of eyes on topical antihypertensive drugs doubled. A slow decrease of RNFL thickness could be observed overtime, although not statistically or clinically relevant (p=0,17). Conclusion The implant has shown to be safe and anatomically efficient over three years for the treatment of DME and it stabilized VA. However, further studies are necessary to understand the predictors of response to FAc implantation and to elucidate the role of RNFL thickness in the prediction of glaucoma in DME eyes.